Growth and yield response of Kenaf (Hibiscus cannabinus L.) seed production to different sowing times (Journal of Bangladesh Academy of Sciences, 2022)
An experiment was conducted during 2020-21 at Jute Research Substation, Jashore, to study growth and seed yield response of kenaf to different sowing times. Seeds were sown from 15 July to 1 October, an interval of 15 days, as treatment variables under RCBD design with three replications. Greater seed yield was obtained from the 1st September sowing, which was at par with 15 September and 15 August sowings values. So, maximum seed production of kenaf may be ensured with optimum seed sowing between the 1st and 15thof September.   J. Bangladesh Acad. Sci. 46(2); 219-221: December 2022